Institutional preconditions of development microfinancings in Russia as specific forms of crediting small and average businesses (Путеводитель предпринимателя)
In recentyears in Russia has the formation and development microfinancing institute. The main reasons development of a given form of financing of small business, consist in insufficiency of providing with financial services of subjects of the small and medium business, raising requirements to capitalization of a banking system and as a result reduction of structure of her participants, and also prospect of expansion of the credit market at the expense of foreign commercial banks in connection with Russia’s accession to the World Trade Organization.